Hepatocytes and neutrophils cooperatively suppress bacterial infection by differentially regulating lipocalin‐2 and neutrophil extracellular traps. Issue 4 (10th May 2018) - Li, Hongjie; Feng, Dechun; Cai, Yan; Liu, Yudong; Xu, Mingjiang; Xiang, Xiaogang; Zhou, Zhou; Xia, Qiang; Kaplan, Mariana J.; Kong, Xiaoni; Gao, Bin
Abstract : Lipocalin‐2 (LCN2), also known as neutrophil gelatinase‐associated lipocalin (NGAL), a key antibacterial protein, is highly elevated in patients with end‐stage liver disease that is often associated with bacterial infection. LCN2 is expressed at high levels in both hepatocytes and neutrophils; however, how hepatocyte‐derived and neutrophil‐derived LCN2 cooperate to combat bacterial infection remains unclear. Here, by studying hepatocyte‐specific and myeloid‐specific Lcn2 knockout mice in two models of systemic and local Klebsiella pneumoniae infections, we demonstrated that hepatocytes played a critical role in controlling systemic infection by secreting LCN2 protein into the circulation following intraperitoneal injection of bacteria, whereas neutrophils were more important in combating local lung infection by carrying LCN2 in their specific granules to the local infection site following intratracheal intubation of bacteria. Both hepatocyte‐derived and myeloid cell–derived LCN2 were required against bacterial infection in the peritoneal cavity and liver necrotic areas following intraperitoneal injection of Klebsiella pneumoniae . LCN2/NGAL protein was detected in neutrophil extracellular traps (NETs) in activated neutrophils from mice and humans. Disruption of the Lcn2 gene in neutrophils abolished LCN2 on NETs, whereas deletion of this gene in hepatocytes did not affect LCN2 protein on NETs. Genetic deletion of the Lcn2 gene globally or specifically in neutrophils did not affect NET formation but reduced the bactericidal effect of NETs in vitro . Finally, NGAL‐positive NETs were detected in the liver from patients with various types of liver diseases. Conclusion : Both hepatocytes and neutrophils combat bacterial infection through the production of LCN2; extracellular LCN2 secreted by hepatocytes limits systemic bacterial infection, whereas neutrophils carry LCN2 protein to the local site and against local bacterial infection through NETs. (Hepatology 2018).